2016
DOI: 10.5603/gp.2016.0002
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography as a predictor of the extent of the disease and surgical outcomes in ovarian cancer

Abstract: Objectives: The aim of the present study is to determine the predictive value of Computed Tomography (CT), alone or in combination with serum CA-125 levels, for preoperative staging, detection of the extent of the disease, and surgical complications in patients with ovarian carcinoma. Material and methods:One hundred and fourteen patients diagnosed with ovarian carcinoma following an exploratory laparotomy with a preoperative CT scan, performed between January 2007 and June 2013, were enrolled in the study. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Metastases of EOC may incidentally grow through the viscera of the bowel or the bladder. 79 The visceral and parietal peritoneal surfaces have a similar structural composition throughout the abdomen. The incidental invasive growth in specific areas, therefore, suggests that the peritoneal microenvironment, or structures that support the peritoneum, play a role in the development of deep invasive growth.…”
Section: Invasion Of Submesothelial Stromamentioning
confidence: 99%
“…Metastases of EOC may incidentally grow through the viscera of the bowel or the bladder. 79 The visceral and parietal peritoneal surfaces have a similar structural composition throughout the abdomen. The incidental invasive growth in specific areas, therefore, suggests that the peritoneal microenvironment, or structures that support the peritoneum, play a role in the development of deep invasive growth.…”
Section: Invasion Of Submesothelial Stromamentioning
confidence: 99%
“…In total, 23 datasets evaluated the presence of PMs in OC with MDCT [26,27,30,52,[56][57][58][59][63][64][65][66][67][68][69][70][71][72][73][74][75][76]78] (Table 4); 2, 3, and 8 studies were performed on a 4-row [52,58], 16-row [56,57,74], and 64-row [27,30,59,63,67,70,72,75] MDCT scanner, respectively, 4 studies used both a 16-row and a 64-row CT [64,66,73,76], and 1 report used a 4-row, a 16-row, and a 64-row [65] CT machine (Table 5). Overall, 20 studies [27,30,52,[56][57][58]...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Overall, 20 studies [27,30,52,[56][57][58][59][63][64][65][66][67][68][69][70][71][72][73][74]76,78] reported the intravenous administration of iodinated contrast medium; 10 of them used the portal phase [27,56-59, 66-68,73,78], 4 used both the arterial and the portal phase [52,65,74,76], 1 used the arterial phase [72], and 1 study used both the portal and the delayed phase [69]. The use of luminal contrast was reported in 15 studies [30,52,[64][65][66][67][68][69][70][71][72][73][74]76,78]; 8 studies reported the oral administration of H 2 O and diluted contrast medium, including iodinated contrast material in 4 reports [30,66,74,…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serous cystic adenocarcinomas may contain microcalcifications. Serous cystic adenomas are usually small and single-celled, whereas mucous cystic adenomas are larger multicellular clusters [13]. Mucinous tumors are attenuated on CT and have heterogeneous signal intensity on T1-weighted and T2-weighted MRI images, which results in the appearance of "stained glass".…”
Section: Ovarian Cancer Fallopian Tubes Primary Peritoneal Cancersmentioning
confidence: 99%